Students' perceptions of the effectiveness of additional language tuition in the University of Cape Town MBChB programme: A descriptive cross-sectional study - Zahraa Mohamed; Stephanie Roche; Joel Claassen; Zukile Jama (AOSIS, 2019)
Background: Language barriers between doctors and patients have been shown globally to negatively affect the quality of health care and infringe on basic patient rights. In response to these challenges, the Division of Family Medicine at the University of Cape Town (UCT) integrated career-oriented Afrikaans and Xhosa communication skills classes into the MBChB degree programme in 2003. Aim: To measure students' perceptions of the effectiveness of the language communication skills classes in creating multilingual medical practitioners in the South African context and compare these perceptions between the Afrikaans and Xhosa courses. Setting: The study was conducted on the Health Sciences campus of the University of Cape Town, South Africa. Methods: The study was a cross-sectional survey. During March 2017, access to an online structured questionnaire was provided to 600 randomly selected medical students from second to sixth year at the UCT. Results: The response rate was 43.7%, and students reported a much higher baseline level of Afrikaans compared to Xhosa (99.0% vs. 42.7%). Respondents reported a lack of confidence in the clinical sphere for both languages (Afrikaans 51.5%; Xhosa 60.0%) and a lack of communicative ability (Afrikaans 35.3%; Xhosa 67.2%) as major barriers to patient communication. Conclusions: Respondents overwhelmingly agreed that second language learning is valuable for their future as medical practitioners, but did not feel that they are developing sufficient communicative competence. The courses need to be re-evaluated to account for the lower level of pre-MBChB Xhosa exposure, as compared to Afrikaans. Increased time allocated to languages, increased attention to cultural issues and informal variants, and redesigning assessments to better reflect students' abilities are all potential recommendations.